Analysis of the Structure and Luminescence Properties of Sr3Y2Ge3O12:0.05Eu3+ (SYGO:Eu3+) According to Judd–ofelt Theory - Lan, Nguyen Mai Cao Hoang Phuong; Kien, Nguyen Duc Trung; Thang, Cao Xuan; Tung, Nguyen Viet (VNU Journal of Science: Mathematics - Physics, 2023)
In this work, SYGO:Eu 3+ red phosphors have been successfully synthesized by sol-gel method. X-ray diffraction analysis showed a cubic crystalline structure of the samples, belonging to a space group of Ia3d (230). Field-emission-scanning electron microscopy (FE-SEM) combined with EDS was performed to determine the microstructure and elemental composition of the fabricated phosphors. The particles in the samples are significantly agglomerated, about ∼200 nm in size. The results of fluorescence properties investigation (PLE-PL) showed that, the maximum emission spectrum at 612 nm under ultraviolet light close to 395 nm for excitation. Calculating the J-O intensity parameters demonstrates that Ω 2 is larger than Ω 4 which proves the asymmetric surrounding local structure of the doped ion. In addition, the luminescence efficiency possesses approximately a value of 70%. This suggests that the fabricated SYGO:Eu 3+ phosphors  can be used as a solid lighting material for WLED.